Preparation method and application of Zr-doped high-entropy Prussian blue sodium-ion battery positive electrode material
Through the preparation method of Zr-doped high-entropy Prussian blue sodium ion battery positive electrode material, the phase instability caused by structural water in the existing materials is solved, and the effects of high energy density, high power density and structural stability are achieved.
Patent Information
- Application Number
- CN202411703912.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-21
AI Technical Summary
The existing Prussian blue sodium ion battery positive electrode material has structural water problems, which leads to instability in the phase state of the material and affects the electrochemical performance.
The preparation method of Zr-doped high-entropy Prussian blue sodium ion battery cathode material is adopted to regulate the nucleation/growth rate and the presence of anion vacancies through ball milling reaction and ultrasonic treatment, reduce structural water, and improve the phase stability of the material.
The phase state stability during sodium ion storage is achieved, the high energy density, high power density and structural stability of the material are improved, and the cycle life of the battery is extended.
Smart Images

Figure HDA0005154067120000011 
Figure HDA0005154067120000012 
Figure HDA0005154067120000021
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a Zr-doped high-entropy Prussian blue sodium ion battery positive electrode material, belonging to the technical field of sodium ion batteries. Background Art
[0002] Sodium and lithium belong to the same main group of elements and have similar chemical and physical properties. Therefore, sodium batteries can serve as a continuation of the lithium-ion battery industry, taking advantage of the abundant reserves and low cost of sodium. However, compared with lithium-ion batteries, sodium ions have poor electrochemical performance due to their larger size and mass. In order to improve this problem, it is necessary to find suitable electrode materials. Prussian blue and its derivatives (PBAs) are a type of substance that has been widely studied as positive electrode materials for sodium-ion batteries. PBAs have an open framework structure and a typical metal-organic framework (MOF). Its lattice presents a face-centered cubic crystal structure, in which Fe—C≡N—M (transition metal) is arranged to form a stable three-dimensional skeleton structure. This structure provides a stable framework and a large number of ion channels, allowing sodium ions to freely enter and exit on the (001) crystal plane. At the same time, by adjusting the types and contents of the constituent elements in PBAs, the matching between transition metal ions and ion composition in the lattice can be improved, lattice defects can be reduced, and positive electrode materials with high energy density and high rate performance can be designed.
[0003] At present, Prussian blue and its derivatives (PBAs) mainly have Fe(CN)6 vacancies. Water molecules will spontaneously enter the vacancies, causing changes in the structure of the material. The presence of vacancies will greatly reduce the active sites and break the electron transfer path. Excess water will hinder the migration of alkali metal ions and react with the electrolyte, causing the material to collapse during the sodium ion intercalation process, which restricts the application of PB and PBAs in sodium ion batteries. Summary of the invention
[0004] In view of the structural water problem of the existing Prussian blue sodium ion battery positive electrode material, the present invention proposes a preparation method and application of a Zr-doped high-entropy Prussian blue sodium ion battery positive electrode material. The present invention utilizes the dual action mechanism of a complexing agent and a high-entropy component to achieve the reduction of its nucleation / growth rate and the regulation of the tendency of N-connected transition metal hydrate ions. By controllably adjusting the presence of anion vacancies and coordinated water molecules, the material can solve the phase stability problem during the sodium ion storage process. At the same time, the positive electrode material has a triple effect of low defects, high entropy stability and multi-element synergy, which enables it to obtain high energy density, high power density and excellent structural stability.
[0005] A method for preparing a Zr-doped high-entropy Prussian blue sodium ion battery positive electrode material, the specific steps are as follows:
[0006] (1) MnSO4·H2O, FeSO4·7H2O, ZnSO4·7H2O, NiSO4·6H2O, Zr(SO4)2·4H2O, sodium citrate and C6FeN6·4Na·10H2O were subjected to ball milling reaction;
[0007] (2) The ball milling reaction product is added to deionized water for ultrasonic treatment, then washed with deionized water and ethanol, and vacuum dried to obtain Zr-doped high entropy Prussian blue sodium ion battery positive electrode material Zr-HEHCF.
[0008] Preferably, in the step (1), the molar ratio of MnSO4·H2O, FeSO4·7H2O, ZnSO4·7H2O, NiSO4·6H2O, Zr(SO4)2·4H2O, C6FeN6·4Na·10H2O, and sodium citrate in mmol:mmol:mmol:mmol:mmol:mmol:mmol is 2:2:2:2:2:2:2 to 6:15:10.
[0009] Preferably, the ball-to-material mass ratio of the ball milling reaction in step (1) is 10:0.5-1, the rotation speed of the ball milling reaction is 100-1000 rpm, and the ball milling time is 2-20 h.
[0010] Preferably, the solid-liquid ratio of the ball milling reaction product to deionized water in step (2) is 1:6-10 g:mL; the ultrasonic frequency is 35 kHz, the ultrasonic temperature is 20-60° C., and the time is 10-30 min.
[0011] Preferably, the vacuum drying temperature in step (2) is 60 to 120° C., and the drying time is 24 to 36 hours.
[0012] The Zr-doped high-entropy Prussian blue sodium ion battery positive electrode material can be used as a positive electrode active material to prepare a sodium ion battery positive electrode: the Zr-doped high-entropy Prussian blue sodium ion battery positive electrode material is used as the positive electrode active material, the positive electrode active material, the conductive agent and the binder are mixed evenly and then coated on the surface of the positive electrode current collector aluminum foil to form a positive electrode material active layer.
[0013] The sodium ion battery positive electrode, the sodium ion battery negative electrode (sodium sheet), the separator (glass fiber (Whatman, GF / A)) and the electrolyte (1M NaClO4 ethylene carbonate and diethyl carbonate (v / v=1:1) solution with 5% fluoroethylene carbonate added as electrolyte) are assembled into a sodium ion battery.
[0014] The beneficial effects of the present invention are:
[0015] (1) The Zr-doped high-entropy Prussian blue sodium ion battery cathode material of the present invention has a face-centered cubic PBAs crystal structure, and the face-centered cubic PBAs crystal structure forms a three-dimensional rigid framework with open ion channels and spacious interstitial spaces, and is rich in redox active sites; the PBAs lattice has abundant ion channels and interstitial spaces, which can accommodate larger alkali metal cations (such as Na + , K + );
[0016] (2) The Zr-doped high-entropy Prussian blue sodium ion battery positive electrode material of the present invention contains less structural water because the material synthesized by dry grinding, the battery composed of the material has the advantages of high reaction efficiency, stable structure, small volume change, etc., and as a sodium ion battery positive electrode, it has the performance of high energy density and long cycle life;
[0017] (3) The Zr-doped high-entropy Prussian blue sodium ion battery cathode material of the present invention not only exhibits a high first-cycle discharge specific capacity, but also has relatively good cycle stability. -1 After 500 cycles at a current density of , the specific capacity remained basically unchanged, and the specific capacity retention rate reached 73.07%. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The sodium ion battery positive electrode material Na of Example 2 1.69 Fe 0.39 Mn 0.38 Ni 0.06 Zn 0.11 Zr 0.06 [Fe(CN)6] 0.89 O 0.11
[0019] 1. XRD pattern of 61H2O (Zr-HEHCF);
[0020] Figure 2 The sodium ion battery positive electrode material Na of Example 2 1.69 Fe 0.39 Mn 0.38 Ni 0.06 Zn 0.11 Zr 0.06 [Fe(CN)6] 0.89 O 0.11
[0021] 1.61H2O (Zr-HEHCF) SEM image;
[0022] Figure 3 The sodium ion battery positive electrode material Na of Example 2 1.69 Fe 0.39Mn 0.38 Ni 0.06 Zn 0.11 Zr 0.06 [Fe(CN)6] 0.89 O 0.11
[0023] CV curve of 1.61H2O (Zr-HEHCF);
[0024] Figure 4 The sodium ion battery positive electrode material Na of Example 2 1.69 Fe 0.39 Mn 0.38 Ni 0.06 Zn 0.11 Zr 0.06 [Fe(CN)6] 0.89 O 0.11
[0025] 1.61H2O (Zr-HEHCF) charge and discharge curves at room temperature;
[0026] Figure 5 The sodium ion battery positive electrode material Na of Example 2 1.69 Fe 0.39 Mn 0.38 Ni 0.06 Zn 0.11 Zr 0.06 [Fe(CN)6] 0.89 O 0.11
[0027] ·1.61H2O (Zr-HEHCF) sodium ion battery cycle performance curves at different rates;
[0028] Figure 6 The sodium ion battery positive electrode material Na of Example 2 1.69 Fe 0.39 Mn 0.38 Ni 0.06 Zn 0.11 Zr 0.06 [Fe(CN)6] 0.89 O 0.11
[0029] ·1.61H2O (Zr-HEHCF) sodium ion battery prepared by constant current cycling performance curve at room temperature. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.
[0031] Example 1: A method for preparing a Zr-doped high-entropy Prussian blue sodium ion battery positive electrode material, the specific steps are as follows:
[0032] A method for preparing a Zr-doped high-entropy Prussian blue sodium ion battery positive electrode material, the specific steps are as follows:
[0033] (1) MnSO4·H2O, FeSO4·7H2O, ZnSO4·7H2O, NiSO4·6H2O, Zr(SO4)2·4H2O, sodium citrate and C6FeN6·4Na·10H2O are added into a ball mill, and the ball milling reaction is carried out at a rotation speed of 120 rpm for 10 hours; the molar ratio of MnSO4·H2O, FeSO4·7H2O, ZnSO4·7H2O, NiSO4·6H2O, Zr(SO4)2·4H2O, C6FeN6·4Na·10H2O and sodium citrate is 2:2:2:2:2:15:10 in mmol:mmol:mmol:mmol:mmol:mmol; and the mass ratio of balls to materials in the ball milling reaction is 10:1;
[0034] (2) The ball milling reaction product was added to deionized water (the solid-liquid ratio of the ball milling reaction product to deionized water was 1:10 g:mL), and ultrasonic treatment was performed at a temperature of 35°C and an ultrasonic frequency of 35 kHz for 30 min. The solid and liquid were separated by centrifugation, and the solid was then washed with deionized water and ethanol in turn, and vacuum dried at a temperature of 60°C for 36 h to obtain Zr-doped high entropy Prussian blue sodium ion battery positive electrode material Zr-HEHCF (Na 1.56 Fe 0.32 Mn 0.37 Ni 0.13 Zn 0.13 Zr 0.05 [Fe(CN)6] 0.81 O 0.19 1.59H2O);
[0035] The Zr-doped high-entropy Prussian blue sodium ion battery cathode material Zr-HEHCF of this embodiment has rich redox active sites, can provide more contacts for the electrolyte and active materials, improve the battery reaction efficiency, and has a three-dimensional rigid framework structure with open ion channels and spacious gap spaces, which can effectively promote the insertion of sodium ions; high-entropy materials have high entropy effects in thermodynamics, hysteresis diffusion effects in kinetics, lattice distortion effects in structure, and "cocktail" effects in performance, which are fully utilized by Zr-HEHCF sodium ion battery cathode materials;
[0036] The Zr-doped high entropy Prussian blue sodium ion battery positive electrode material Zr-HEHCF can be used as a positive electrode active material to prepare a sodium ion battery positive electrode: the Zr-doped high entropy Prussian blue sodium ion battery positive electrode material Zr-HEHCF is used as a positive electrode active material, the positive electrode active material, a conductive agent (SP) and a binder (PVDF) are mixed uniformly in a mass ratio of 7:2:1, and then coated on the surface of a positive electrode current collector aluminum foil to form a positive electrode material active layer;
[0037] In this embodiment, sodium metal is used as the negative electrode sheet, glass fiber (Whatman, GF / A) is used as the separator, the electrolyte is composed of 1M NaClO4 ethylene carbonate and diethyl carbonate (volume ratio is 1:1) solution, and fluoroethylene carbonate is added (the mass concentration of fluoroethylene carbonate in the electrolyte is 5%), aluminum foil is used as the positive electrode current collector, and a 12mm positive electrode material active layer (active component Zr doped high entropy Prussian blue sodium ion battery positive electrode material Zr-HEHCF (70wt.%), conductive agent (SP) (20wt.%), binder (PVDF) (10wt.%)) is coated on the surface of the aluminum foil to form a positive electrode sheet, which is assembled into a sodium ion battery to optimize the performance of the sodium ion battery, including improving the energy density, cycle stability and reaction efficiency of the battery;
[0038] Sodium ion battery with 0.3Ag -1 After 500 cycles, the discharge capacity can still maintain about 48.52 mAh g -1 The specific capacity retention rate reaches 63.54%, and it has good cycle stability. The material utilizes the high entropy effect in thermodynamics of high entropy materials, the hysteresis diffusion effect in kinetics, the lattice distortion effect in the structure, the "cocktail" effect in performance, and the synergistic effect in performance to improve its performance in the battery.
[0039] Example 2: A method for preparing a Zr-doped high-entropy Prussian blue sodium ion battery positive electrode material, the specific steps are as follows:
[0040] A method for preparing a Zr-doped high-entropy Prussian blue sodium ion battery positive electrode material, the specific steps are as follows:
[0041] (1) MnSO4·H2O, FeSO4·7H2O, ZnSO4·7H2O, NiSO4·6H2O, Zr(SO4)2·4H2O, sodium citrate and C6FeN6·4Na·10H2O are added into a ball mill, and the ball milling reaction is carried out at a rotation speed of 300 rpm for 14 hours; the molar ratio of MnSO4·H2O, FeSO4·7H2O, ZnSO4·7H2O, NiSO4·6H2O, Zr(SO4)2·4H2O, C6FeN6·4Na·10H2O and sodium citrate is 2:2:2:2:4:15:10 in mmol:mmol:mmol:mmol:mmol:mmol; and the mass ratio of balls to materials in the ball milling reaction is 15:1;
[0042] (2) The ball milling reaction product was added to deionized water (the solid-liquid ratio of the ball milling reaction product to deionized water was 1:6 g:mL), and ultrasonic treatment was performed at a temperature of 45°C and an ultrasonic frequency of 35 kHz for 20 min. The solid and liquid were separated by centrifugation, and the solid was then washed with deionized water and ethanol in turn, and vacuum dried at a temperature of 120°C for 24 h to obtain Zr-doped high entropy Prussian blue sodium ion battery positive electrode material Zr-HEHCF (Na 1.69 Fe 0.39 Mn 0.38 Ni 0.06 Zn 0.11 Zr 0.06 [Fe(CN)6] 0.89 O 0.11 1.61H2O);
[0043] The XRD spectrum of Zr-HEHCF, the positive electrode material of Zr-doped high entropy Prussian blue sodium ion battery in this embodiment, is shown in Figure 1 ,from Figure 1 It can be seen that the peak shape is relatively sharp, indicating that the prepared positive electrode material has a higher degree of crystallinity, a smaller grain size, a larger specific surface area, and more reactive active sites;
[0044] The SEM image of Zr-HEHCF, the positive electrode material of Zr-doped high entropy Prussian blue sodium ion battery in this embodiment, is shown in FIG. Figure 2 ,from Figure 2 It can be seen that the Zr-HEHCF sodium ion battery cathode material is a three-dimensional stacking structure with relatively regular spherical nanoparticles with a diameter of about 20 to 90 nm and a small particle size;
[0045] The Zr-doped high-entropy Prussian blue sodium ion battery cathode material Zr-HEHCF of this embodiment has rich redox active sites, can provide more contacts for the electrolyte and active materials, improve the battery reaction efficiency, and has a three-dimensional rigid framework structure with open ion channels and spacious gap spaces, which can effectively promote the insertion of sodium ions; high-entropy materials have high entropy effects in thermodynamics, hysteresis diffusion effects in kinetics, lattice distortion effects in structure, and "cocktail" effects in performance, which are fully utilized by Zr-HEHCF sodium ion battery cathode materials;
[0046] The Zr-doped high entropy Prussian blue sodium ion battery positive electrode material Zr-HEHCF can be used as a positive electrode active material to prepare a sodium ion battery positive electrode: the Zr-doped high entropy Prussian blue sodium ion battery positive electrode material Zr-HEHCF is used as a positive electrode active material, the positive electrode active material, a conductive agent (SP) and a binder (PVDF) are mixed uniformly in a mass ratio of 7:2:1, and then coated on the surface of a positive electrode current collector aluminum foil to form a positive electrode material active layer;
[0047] In this embodiment, sodium metal is used as the negative electrode sheet, glass fiber (Whatman, GF / A) is used as the separator, the electrolyte is composed of 1M NaClO4 ethylene carbonate and diethyl carbonate (volume ratio is 1:1) solution, and fluoroethylene carbonate is added (the mass concentration of fluoroethylene carbonate in the electrolyte is 5%), aluminum foil is used as the positive electrode current collector, and a 12mm positive electrode material active layer (active component Zr doped high entropy Prussian blue sodium ion battery positive electrode material Zr-HEHCF (70wt.%), conductive agent (SP) (20wt.%), binder (PVDF) (10wt.%)) is coated on the surface of the aluminum foil to form a positive electrode sheet, which is assembled into a sodium ion battery to optimize the performance of the sodium ion battery, including improving the energy density, cycle stability and reaction efficiency of the battery;
[0048] The CV curve of the potassium ion battery prepared by Zr-HEHCF, a positive electrode material of a sodium ion battery doped with Zr, is shown in FIG. Figure 3 ,from Figure 3 It can be seen that in the voltage range of 2 to 4.2V, the -1 The scan rate was cyclically tested, and an oxidation peak appeared at about 3.41V and a reduction peak appeared at about 3.05V.
[0049] The charge and discharge curves of the potassium ion battery prepared by the Zr-HEHCF positive electrode material of the Zr-doped high entropy Prussian blue sodium ion battery in this example at room temperature are shown in FIG. Figure 4 ,from Figure 4 It can be seen that within the 2-4.2V voltage window, with 15mAg -1 The current density was used for charge and discharge cycle test, and the first discharge capacity was as high as 86.9 mAh g-1 ; The second discharge capacity is 85.7 mAhg -1 ; The 27th discharge capacity is 73mAhg -1 , stable charging and discharging;
[0050] The constant current cycle performance curves of the sodium ion battery of this embodiment at different rates at room temperature are shown in Figure 6 ,from Figure 6 It can be seen that five consecutive cycle tests were carried out at rates of 1.5C, 3C, 7.5C, 15C, and 30C, and the corresponding specific capacity was 72.3 mAh g -1 、65.7mAhg -1 、58.1mAhg -1 、51.6mAhg -1 、43.3mAhg -1 When the charge and discharge is changed from 30C to 1.5C again, the specific capacity is almost the same as before, indicating that the positive electrode material of this sodium ion battery has high rate capability and stable cycle.
[0051] The constant current cycle performance curve of the sodium ion battery in this embodiment at room temperature is shown in Figure 6 ,from Figure 6 It can be seen that within the voltage window of 2 to 4.2 V, 0.3 Ag -1 The current density was used for cycle testing; during the first cycle, the discharge capacity was about 72.4 mAh g -1 During the second cycle, the discharge capacity decreased slightly to about 72 mAh g -1 After 500 cycles, the discharge capacity can still maintain about 52.9 mAh g -1 The specific capacity of the material is 73.07%, and the specific capacity retention rate is 73.07%. The material makes full use of the high entropy effect in thermodynamics of high entropy materials, the hysteresis diffusion effect in kinetics, the lattice distortion effect in the structure, and the "cocktail" effect in performance. These characteristics make the positive electrode material show excellent performance and cycle stability in sodium ion batteries.
[0052] Therefore, the sodium ion battery in this embodiment uses Zr-doped high entropy Prussian blue sodium ion battery positive electrode material Zr-HEHCF as the sodium ion battery positive electrode, which not only shows a high discharge capacity in the first cycle, but also has relatively good cycle stability. -1 After 500 cycles at a current density of , the specific capacity remains basically unchanged, and the specific capacity retention rate reaches 73.07%, indicating that the sodium ion battery has good cycle stability and capacity retention performance.
[0053] Example 3: A method for preparing a Zr-doped high-entropy Prussian blue sodium ion battery positive electrode material, the specific steps are as follows:
[0054] A method for preparing a Zr-doped high-entropy Prussian blue sodium ion battery positive electrode material, the specific steps are as follows:
[0055] (1) MnSO4·H2O, FeSO4·7H2O, ZnSO4·7H2O, NiSO4·6H2O, Zr(SO4)2·4H2O, sodium citrate and C6FeN6·4Na·10H2O are added into a ball mill, and the ball milling reaction is carried out at a rotation speed of 800 rpm for 16 hours; the molar ratio of MnSO4·H2O, FeSO4·7H2O, ZnSO4·7H2O, NiSO4·6H2O, Zr(SO4)2·4H2O, C6FeN6·4Na·10H2O and sodium citrate is 2:2:2:2:6:15:10 in mmol:mmol:mmol:mmol:mmol:mmol; and the ball-to-material mass ratio of the ball milling reaction is 18:1;
[0056] (2) The ball milling reaction product was added to deionized water (the solid-liquid ratio of the ball milling reaction product to deionized water was 1:8 g:mL), and ultrasonic treatment was performed at a temperature of 55°C and an ultrasonic frequency of 35 kHz for 10 min. The solid and liquid were separated by centrifugation, and the solid was then washed with deionized water and ethanol in turn, and vacuum dried at a temperature of 100°C for 28 h to obtain Zr-doped high entropy Prussian blue sodium ion battery positive electrode material Zr-HEHCF (Na 1.71 Fe 0.32 Mn 0.27 Ni 0.18 Zn 0.11 Zr 0.12 [Fe(CN)6] 0.91 O 0.09 1.56H2O);
[0057] The Zr-doped high-entropy Prussian blue sodium ion battery cathode material Zr-HEHCF of this embodiment has rich redox active sites, can provide more contacts for the electrolyte and active materials, improve the battery reaction efficiency, and has a three-dimensional rigid framework structure with open ion channels and spacious gap spaces, which can effectively promote the insertion of sodium ions; high-entropy materials have high entropy effects in thermodynamics, hysteresis diffusion effects in kinetics, lattice distortion effects in structure, and "cocktail" effects in performance, which are fully utilized by Zr-HEHCF sodium ion battery cathode materials;
[0058] The Zr-doped high entropy Prussian blue sodium ion battery positive electrode material Zr-HEHCF can be used as a positive electrode active material to prepare a sodium ion battery positive electrode: the Zr-doped high entropy Prussian blue sodium ion battery positive electrode material Zr-HEHCF is used as a positive electrode active material, the positive electrode active material, a conductive agent (SP) and a binder (PVDF) are mixed uniformly in a mass ratio of 7:2:1, and then coated on the surface of a positive electrode current collector aluminum foil to form a positive electrode material active layer;
[0059] In this embodiment, sodium metal is used as the negative electrode sheet, glass fiber (Whatman, GF / A) is used as the separator, the electrolyte is composed of 1M NaClO4 ethylene carbonate and diethyl carbonate (volume ratio is 1:1) solution, and fluoroethylene carbonate is added (the mass concentration of fluoroethylene carbonate in the electrolyte is 5%), aluminum foil is used as the positive electrode current collector, and a 12mm positive electrode material active layer (active component Zr doped high entropy Prussian blue sodium ion battery positive electrode material Zr-HEHCF (70wt.%), conductive agent (SP) (20wt.%), binder (PVDF) (10wt.%)) is coated on the surface of the aluminum foil to form a positive electrode sheet, which is assembled into a sodium ion battery to optimize the performance of the sodium ion battery, including improving the energy density, cycle stability and reaction efficiency of the battery;
[0060] Sodium ion battery with 0.3Ag -1 After 500 cycles, the discharge capacity can still maintain about 54.8 mAh g -1 The specific capacity retention rate reaches 82.78%, and it has excellent cycle stability; the material utilizes the high entropy effect in thermodynamics of high entropy materials, the hysteresis diffusion effect in kinetics, the lattice distortion effect in the structure, the "cocktail" effect in performance, and the synergistic effect in performance to improve its performance in the battery.
[0061] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A method for preparing a Zr-doped high-entropy Prussian blue sodium ion battery positive electrode material, characterized in that: The specific steps are as follows: (1) MnSO4·H2O, FeSO4·7H2O, ZnSO4·7H2O, NiSO4·6H2O, Zr(SO4)2·4H2O, sodium citrate and C6FeN6·4Na·10H2O were subjected to ball milling reaction; (2) The ball milling reaction product is added to deionized water for ultrasonic treatment, then washed with deionized water and ethanol, and vacuum dried to obtain a Zr-doped high-entropy Prussian blue sodium ion battery positive electrode material.
2. The method for preparing the Zr-doped high-entropy Prussian blue sodium ion battery positive electrode material according to claim 1, characterized in that: In step (1), the molar ratio of MnSO4·H2O, FeSO4·7H2O, ZnSO4·7H2O, NiSO4·6H2O, Zr(SO4)2·4H2O, C6FeN6·4Na·10H2O and sodium citrate, mmol:mmol:mmol:mmol:mmol:mmol:mmol, is 2:2:2:2:2:2:2 to 6:15:
10.
3. The method for preparing the Zr-doped high-entropy Prussian blue sodium ion battery positive electrode material according to claim 1, characterized in that: The ball-to-material mass ratio of the ball milling reaction in step (1) is 10:0.5-1, the rotation speed of the ball milling reaction is 100-1000 rpm, and the ball milling time is 2-20 hours.
4. The method for preparing the Zr-doped high-entropy Prussian blue sodium ion battery positive electrode material according to claim 1, characterized in that: The solid-liquid ratio of the ball milling reaction product to deionized water in step (2) is 1:6 to 10 g:mL; the ultrasonic frequency is 35 kHz, the ultrasonic temperature is 30 to 60° C., and the time is 10 to 30 min.
5. The method for preparing the Zr-doped high-entropy Prussian blue sodium ion battery positive electrode material according to claim 1, characterized in that: The vacuum drying temperature in step (2) is 60 to 120° C., and the drying time is 24 to 36 hours.
6. The Zr-doped high entropy Prussian blue sodium ion battery positive electrode material prepared by the method according to any one of claims 1 to 5 is used as a positive electrode active material to prepare a sodium ion battery positive electrode.
Citation Information
Cited By
Preparation method and application of high-entropy Prussian blue positive electrode material
CN120646863A